Laryngeal Preservation in Managing Advanced Tracheal Adenoid Cystic Carcinoma - Thavakumar Subramaniam; Paul Lennon; John Kinsella; James Paul O’Neill (Case Reports in Otolaryngology)
A 37-year-old male athlete was diagnosed with primary tracheal adenoid cystic carcinoma following investigation for dyspnea, wheeze, and eventual stridor. Preoperative bronchoscopy revealed a highly vascular tumor 4 cm distal to the cricoid with no gross disease extending to the carina. Imaging revealed circumferential tracheal irregularity immediately inferior to the cricoid, with no definite cricoid invasion. Locoregional extension of disease was noted invading the thyroid and abutment of the carotid approximately 180°. Intraoperative findings identified tracheal mucosal disease extending distal to the carina and proximally at the cricothyroid joints where bilateral functional recurrent nerves were preserved. A decision made to preserve the larynx given the inability to fully resect distal tracheal disease. A 5 cm sleeve resection of the trachea was made with a cricotracheal anastomosis following suprahyoidal muscle release and laryngeal drop-down. The patient was treated with adjuvant radiotherapy including platinum based chemotherapy in an effort to maximise local control. PET scanning three months after therapy revealed no FDG uptake locally or distally.